2008
DOI: 10.1007/s11610-007-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty for the stiff knee

Abstract: The underlying cause of stiffness must be carefully evaluated when considering total knee arthrolasty for the stiff knee. Any previous skin incision must be recorded as well as the state of the extensor mechanism. The choice of prosthesis constraint should be decided on the state of the soft-tissues often released extensively to gain flexion. A quadriceps release or plasty and a tibial tubercle osteotomy are the current options for exposure, soft-tissue release and bone cuts. Postoperatively, the motion should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been shown that knee patients adapt their gait pattern to regain stability. 2,20,24 Studies reported a 13% reduced speed in patients with moderate osteoarthritis, 25 a 9% decreased cadence in patients with rheumatoid arthritis, 26 and a 9% decrease in stride length in patients operated for severe primary degenerative arthritis of a single knee joint. 3 Quite the same changes were measured with AGA during the simulated functional knee limitations, which measured a 10%Y14% decreased walking speed, a 3%Y7% reduced cadence, and a 7%Y9% reduced step length.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that knee patients adapt their gait pattern to regain stability. 2,20,24 Studies reported a 13% reduced speed in patients with moderate osteoarthritis, 25 a 9% decreased cadence in patients with rheumatoid arthritis, 26 and a 9% decrease in stride length in patients operated for severe primary degenerative arthritis of a single knee joint. 3 Quite the same changes were measured with AGA during the simulated functional knee limitations, which measured a 10%Y14% decreased walking speed, a 3%Y7% reduced cadence, and a 7%Y9% reduced step length.…”
Section: Discussionmentioning
confidence: 99%